2005
DOI: 10.1897/04-045r.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, temporal, and dietary determinants of organic contaminants in nestling tree swallows in Point Pelee National Park, Ontario, Canada

Abstract: Point Pelee National Park of Canada in southwestern Ontario, an important migratory route and vital breeding area for many birds, has localized areas of organochlorine (OC) pesticide contamination from agricultural production during the 1950s and 1960s. During 2001 and 2002, we investigated movement of persistent contaminants through the food web with the insectivorous tree swallow (Tachycineta bicolor) as a sentinel. The a priori site classifications, contaminated or reference, were based on soil residues of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…When feasible, it is important to quantify site-specific dietary composition since variations in prey selection can influence dietary exposure estimates (Neigh et al 2006a;Papp et al 2007;Smits et al 2005). Literature-based estimates of tree swallow ingestion of Dipterans were 15-20% (ww; Johnson and Lombardo 2000;McCarty and Winkler 1999;Neigh et al 2006a) compared to 52% in the current study.…”
Section: Dietary Compositionmentioning
confidence: 50%
See 4 more Smart Citations
“…When feasible, it is important to quantify site-specific dietary composition since variations in prey selection can influence dietary exposure estimates (Neigh et al 2006a;Papp et al 2007;Smits et al 2005). Literature-based estimates of tree swallow ingestion of Dipterans were 15-20% (ww; Johnson and Lombardo 2000;McCarty and Winkler 1999;Neigh et al 2006a) compared to 52% in the current study.…”
Section: Dietary Compositionmentioning
confidence: 50%
“…Profiles of the relative concentrations of individual PCDD/DF congeners in samples of invertebrates and bolus at SAs on the Tittabawassee River downstream of the source of contamination were dominated by 1,2,3,4,6,7,8,9Introduction Site-specific dietary exposure to polychlorinated dibenzofurans (PCDFs) and polychlorinated dibenzo-p-dioxins (PCDDs) was determined for three cavity-nesting, insectivorous passerine species downstream of Midland, Michigan (USA). Tree swallows (Tachycineta bicolor), which eat primarily emergent aquatic invertebrates (McCarty 1997;McCarty and Winkler 1999;Mengelkoch et al 2004), have been shown to have exposure links to contaminated sediments (Custer et al 1998;Echols et al 2004;Maul et al 2006;Neigh et al 2006c;Papp et al 2007;Smits et al 2005). House wrens (Troglodytes aedon) and eastern bluebirds (Sialia sialis) have been used to assess the contaminant exposure of terrestrial insectivores at locations with contaminated soils (Neigh et al 2006a).…”
mentioning
confidence: 99%
See 3 more Smart Citations